Multimodal Imaging in Uveitis (Springer International Publishing, 2018)
This book is a comprehensive guide to the imaging techniques that have revolutionized the diagnosis and management of uveitis during the past decade, including optical coherence tomography (OCT), enhanced depth imaging, fundus autofluorescence, and wide-field angiography. In addition, the current role of the traditional (invasive) gold standard techniques, fluorescein angiography and indocyanine green angiography, is described. Among the newer imaging modalities, detailed attention is paid to the various OCT technologies such as spectral domain OCT, enhanced-depth imaging OCT, and enface swept-source OCT. Further individual chapters focus on imaging using adaptive optics, multiview OCT, and OCT angiography. Uveitis can affect virtually any structure in the eye, and imaging of these structures is critical in the diagnosis, prognosis, and management of the disease. Increasing use and better understanding of the different modalities described in this book are sure to improve our knowledge of disease mechanisms and likely outcomes.